Unveiling the causal interactions among the US monetary policy uncertainty, exchange market pressure, and FDI-flows in large emerging market economies - Olanipekun, Ifedolapo Olabisi; Olasehinde-Williams, Godwin (Wiley, 2022)
This study shows how exchange market pressure, FDI inflow, and FDI outflow in large emerging market economies interact with monetary policy uncertainty from the United States (US). A panel of 14 countries were examined using bootstrap Granger causality procedure that captures cross-sectional dependence, reflecting the shared developmental features among emerging economies. In the panel of countries, two-way relationships were unveiled between the US monetary policy uncertainty and exchange market pressure, between the US monetary policy uncertainty and FDI inflow, between the US monetary policy uncertainty and FDI outflow, between the exchange market pressure and FDI inflow, and between the exchange market pressure and FDI outflow. However, there are variations in country-specific results. Most importantly, a feedback relationship exists between the US monetary policy uncertainty and exchange market pressure in two countries, while one-way causality runs from monetary policy uncertainty to exchange market pressure in five countries and from exchange market pressure to monetary policy uncertainty in two countries. No causality was found in five countries. Causality also flows from US monetary policy uncertainty to FDI inflow in six countries and to FDI outflow in one country.
Keywords: exchange market pressure; large emerging market economies; monetary policy uncertainty; the United States (US)